2011
DOI: 10.1073/pnas.1107017108
|View full text |Cite
|
Sign up to set email alerts
|

Wip1 promotes RUNX2-dependent apoptosis in p53-negative tumors and protects normal tissues during treatment with anticancer agents

Abstract: The inactivation of the p53 tumor suppressor pathway in many cancers often increases their resistance to anticancer therapy. Here we show that a previously proposed strategy directed to Wip1 inhibition could be ineffective in tumors lacking p53. On the contrary, Wip1 overexpression sensitized these tumors to chemotherapeutic agents. This effect was mediated through interaction between Wip1 and RUNX2 that resulted, in response to anticancer treatment, in RUNX2-dependent transcriptional induction of the proapopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 55 publications
3
48
0
Order By: Relevance
“…26 We recently reported that elevated levels of Wip1 phosphatase increased the sensitivity of p53-negative tumor cells to chemotherapeutic agents through increasing the Bax/Bcl-x L ratio, a critical factor regulating execution of the apoptotic program. 27 Here, we provide additional evidence that Wip1 overexpression individually affects Bax and Bcl-x L levels by distinct mechanisms. These findings suggest that the biological properties of Wip1 as a stress-responsive phosphatase may provide the basis for improved anticancer therapy of p53-negative tumors.…”
Section: Overexpression Of Wip1 Affectsmentioning
confidence: 76%
See 3 more Smart Citations
“…26 We recently reported that elevated levels of Wip1 phosphatase increased the sensitivity of p53-negative tumor cells to chemotherapeutic agents through increasing the Bax/Bcl-x L ratio, a critical factor regulating execution of the apoptotic program. 27 Here, we provide additional evidence that Wip1 overexpression individually affects Bax and Bcl-x L levels by distinct mechanisms. These findings suggest that the biological properties of Wip1 as a stress-responsive phosphatase may provide the basis for improved anticancer therapy of p53-negative tumors.…”
Section: Overexpression Of Wip1 Affectsmentioning
confidence: 76%
“…Although we observed some reduction in Chk1 phosphorylation upon overexpression of Wip1, the Chk1-regulated G 2 /M checkpoint was not compromised, and the treated cells failed to reach mitosis. 27 Thus, under our experimental conditions, the increased dephosphorylation of Chk1 by Wip1 did not promote mitotic cell death.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Conversely, previous studies have revealed that chemotherapy resistance induced by Wip1 is dependent on the presence of wild-type p53; however, in p53-negative cell lines, Wip1 sensitizes tumor cells to chemotherapeutic drugs by regulating the B-cell lymphoma-2 associated X protein:B-cell lymphoma-extra large ratio and runt related transcription factor-2 and protects normal tissues ( Fig. 1) (55,56). Therefore, Wip1 inhibition is a potential therapeutic target in bladder cancer with preserved wild-type p53, but the reverse effect may occur in p53-negative tumors; however, this remains to be elucidated.…”
Section: Wip1 In Bladder Cancermentioning
confidence: 99%